2009
DOI: 10.1002/cncr.24386
|View full text |Cite
|
Sign up to set email alerts
|

The cancer Support Person's Unmet Needs Survey

Abstract: BACKGROUND: A rigorous psychometric methodology was used to develop a measure of unmet needs for cancer survivors' principal support persons. Principal support person was defined as “someone you can count on and who helps you with your needs.” METHODS: Development of the domains and the items followed an extensive literature review, iterative input from support persons, and consultation with health professionals and front‐line staff working with cancer survivors and their supports. Cognitive interviews helped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
77
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 24 publications
2
77
1
6
Order By: Relevance
“…The questions were similar to those in other unmet needs surveys [31,32], so this finding may reflect the particular poignancy and emotional strain of supporting a young person with cancer. The respondents indicated an overwhelming preference for completing the measure at home, and 87% or more were supportive of survey results being fed back to cancer Proportion who selected agree/strongly agree for each option (%) Fig.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The questions were similar to those in other unmet needs surveys [31,32], so this finding may reflect the particular poignancy and emotional strain of supporting a young person with cancer. The respondents indicated an overwhelming preference for completing the measure at home, and 87% or more were supportive of survey results being fed back to cancer Proportion who selected agree/strongly agree for each option (%) Fig.…”
Section: Discussionmentioning
confidence: 67%
“…The more recent Cancer Support Person's Unmet Needs Survey (SPUNS) assesses the needs of the primary support person, as identified by the person with cancer [31]. The validation study for the SPUNS questionnaire reported that it was psychometrically robust with high internal consistency and adequate face, content and construct validity [31].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Most of the gp rss (96%) and fn rss (91%) who were interviewed or took part in focus groups also completed 16,17 . Both instruments are self-report questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…It is among the most challenging aspects of the oncologist's professional role [1,2] and a source of substantial professional stress [3][4][5][6]. Patients with advanced and incurable cancer are dealing with the emotional impact of a life-threatening illness, complex treatment decisions with often limited likelihood of major benefit, and the challenges of balancing the maintenance of hope with realistic goals [7][8][9].…”
mentioning
confidence: 99%